Diseño en un plan operativo de gestión enérgetica a partir de la evaluación de la eficiencia en refrigeradoras de los clientes residenciales de la ciudad de Latacunga en el año 2013. - Saavedra Acosta, Carlos Eduardo (2013)
In this paper a documentary and field study of the energy demand of the ancient and modern refrigerators, which are in the urban area of Latacunga city, in order to determine the actual consumption of electricity was made, was characterized inefficient refrigerators with more than ten years of operation and refrigerators with current technology. Supported by the results of surveys of the selected sample, the habits of electricity use in homes in Latacunga city have been determined. With consumption data obtained at the entrance to the ancient and modern refrigerators were evaluated by determining their true energy requirements, defining by VAN and TIR. An Operational Energy Management Plan for the city of Latacunga and applicable to any sector where it has the type of appliances studied with the use of the criterion will be improved and power consumption is reduced by the proposed residential customer. The plan includes the recovery of raw materials and controlled destruction of unused components to reduce environmental impact